Rendimento no desdobro de toras de itaúba (Mezilaurus itauba) e tauari (Couratari guianensis) segundo a classificação da qualidade da tora - Garcia, Felipe Manente [UNESP]; Manfio, Daniel Rubert; Sansígolo, Claudio Angeli [UNESP]; Magalhães, Patricia Amanda Domingues [UNESP] (FapUNIFESP (SciELO), 2012)
Residues generated from wood processing and transformation result in a considerable waste of raw material, which adds no value to such noble good. The purpose of this study was to determine the yield of sawn timber from Itaúba (Mezilaurus itauba) and Tauarí (Couratari guianensis) species. To this end, the volumetry and yield percentage of three logs from each species were classified and calculated. The Tauarí species resulted in yields for logs 1, 2 and 3, of 49.70% to 50.28% 39.20%, respectively; while for the Itaúba species, the yields for logs 1, 2 and 3 were of 51.03%; 50.29%; and 47.60%, respectively. It was not possible to verify whether the classification of log quality have influenced the yield.
Yield of itaúba (mezilaurus itauba) and tauarí (couratari guianensis) logs sawmill according to log quality classification
Keywords: Classification.; Sawmill; Yield